“Classy” Trubači: Economies of “Othering” and the Balkan Brass Bands in Slovenia - Hofman, Ana (Department of fine arts, University of Kelaniya Sri Lanka, 2023)
This paper addresses Slovenian brass bands (Slovenski trubači) that flourished on the music scene after 2000 (Kovačič 2009; Hofman 2011; Šivic 2013). In analyzing the case study of selected brass bands, I explore how the label of trubači circulates as an empty signifier filled with different sounds, performance practices, and meanings depending on the market demands. As meeting clients’ expectations is the utmost goal of their labor, brass bands draw on the long-standing imagination of translocality of trubači attached to ethnoracial imaginations of Roma and the tropes of “Balkan,” “Gypsy,” and “Serbian.” In my examination, however, I do not discuss how musicians capitalize on their or others’ identity of Slovenian, Romani, Serbian, Balkan, or Yugoslav, but how the very mechanisms that establish those categories are constituted by the neoliberal market and its demand for flexibility and adaptability. In other words, I focus on a neoliberal entrepreneurial ethos that has been aggressively introduced in the territories of former Yugoslavia after its dissolution, as the most important channel for constructing the sound and imagination of trubači in the region. In doing that, I tend to complement the existent transnational approaches to the World music scene under the label of Gipsy Brass, Balkan Romani Balkan Beat or Balkan music that has been the subject of extensive critical scholarly discussions of essentialization, commodification and appropriation of Roma music by the global North (Silverman 1988, 2007, 2013; Marković 2012, 2015). The questions I pose in this paper are: How does the label of trubači circulate in the national music market in Slovenia? What strategies do bands use to target “the ordinary listener” and to attract the broadest possible audience? How, in the constant adjustment to clients’ needs and their demands for “the best party,” do bands utilize the discourses of ethno-racial difference?